2003
DOI: 10.1289/ehp.5304
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to 4-tert-octylphenol accelerates sexual differentiation and disrupts expression of steroidogenic factor 1 in developing bullfrogs.

Abstract: Sex-specific gonadal steroidogenesis during development is critical to differentiation of the sexually dimorphic phenotype and reproductive function of adult organisms. Environmental contaminants may affect the process of sexual differentiation through disruption of steroid production and/or action. Control of the steroidogenic metabolic pathway is regulated partly by P450 cytochrome hydroxylases, and the expression of many of these enzymes is controlled by the orphan nuclear receptor, steroidogenic factor-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Thus, OP in the aquatic environment may exert toxic effects on amphibians during their embryonic, larval, and adult life cycle stages. Due to its structural similarity to estrogen, OP can induce the transcription of estrogen-responsive genes and thus exert adverse effects on the embryonic development, sexual behavior, and sexual differentiation of amphibians (Nishimura et al, 1997;Kloas et al, 1999;Lutz and Kloas, 1999;Mayer et al, 2003;Huang et al, 2005;Porter et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, OP in the aquatic environment may exert toxic effects on amphibians during their embryonic, larval, and adult life cycle stages. Due to its structural similarity to estrogen, OP can induce the transcription of estrogen-responsive genes and thus exert adverse effects on the embryonic development, sexual behavior, and sexual differentiation of amphibians (Nishimura et al, 1997;Kloas et al, 1999;Lutz and Kloas, 1999;Mayer et al, 2003;Huang et al, 2005;Porter et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Control animals received an equivalent amount of 95% EtOH vehicle. All animals were treated for 96 hours since previous studies demonstrated as little as 24 hours of treatment with OP was sufficient to induce shifts in SF-1 protein concentration (Mayer et al, 2003). Because concentrations may change during the 96 hour exposure time, after the first 48 hours of treatment, 90% of the water in each tank was changed with re-application of test chemicals also at 90% of the original nominal concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…An example is the alkylphenolic pollutant, 4- tert -octylphenol (OP) (Sharma et al, 2009; Ying et al, 2002) that is detected in the plasma and adipose tissue within human populations (Calafat et al, 2008; Inoue et al, 2000; Lopez-Espinosa et al, 2009; Ying et al, 2002). Across a wider range of vertebrate species the observed biological effects of OP exposure are multifold and may include altered gene and/or protein expression in gonadal and pituitary tissues (Lee et al, 2006; Majdic et al, 1997; Mayer et al, 2003; Rhee et al, 2009), abnormal steroid production (Mikkila et al, 2006; Myllymaki et al, 2005b), sperm abnormalities, changes in testicular function (Herath et al, 2004; Kinnberg and Toft, 2003; Rey et al, 2009;) Blake et al, 2004), and impaired sexual differentiation and fertility (Rasmussen et al, 2002; Seki et al, 2003; Karels et al, 2003). Thus, investigation of the biological outcome following treatment of a sentinel species with OP represents a useful model for exposure to estrogenic substances prevalent within the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline data for abnormalities have been gathered, together with changes in abnormality rates over time (Schoff et al 2003). Abnormalities, such as retarded gonadal development (gonadal dysgenesis) and testicular oogenesis (hermaphroditism) that could ultimately influence adult reproductive function, have been found to be the result of the action of EDCs (Colborn et al 1993;Hayes et al 2003;Mayer et al 2003), in contrast to a genetic basis for the deformity (Duijf et al 2003). For example, Kassim et al (1997) found that flutamide caused developmental abnormalities in rat testes, with asymmetry as one characteristic.…”
Section: Introductionmentioning
confidence: 99%